Factors Affecting Sustainability of alternatives livelihood in coastal community of Nembrala East Nusa Tenggara: An Application of MICMAC Method - Paulus, Chaterina Agusta; Fauzi, Akhmad (Universitas Muhammdaiyah Surakarta, 2017)
Coastal communities are known to prone to vulnerability arising from their nature of work. As they are mostly working as fishermen, natural hazards, isolation and climate variabilities are often constraining their ability to obtain sufficient income to support their livelihood. Hence, finding sustainable alternatives source of income is a sensible way to cope with such uncertainty and vulnerability. Achieving sustainable income, nevertheless, is challenging issue since it is affected by various factors from socio-economic as well as institutional perspectives. This paper is an attempt to assess the issue of alternative livelihood by identifying key variables affecting its sustainability. A MICMAC method was used and key variables from the analysis were then identified to support sustainable alternative livelihood in the communities. Lessons learned were also drawn from this study for policy makers and fisheries authorities in the regions.